2016
DOI: 10.1136/neurintsurg-2016-012634
|View full text |Cite
|
Sign up to set email alerts
|

Successful recanalization in acute basilar artery occlusion treated with endovascular therapy is independent of thrombus length

Abstract: Successful recanalization does not depend on thrombus length in patients with BAO treated with EVT. Recanalization can therefore be achieved despite high clot burden. Additionally, a high density of thrombi was a strong predictor of a favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
(30 reference statements)
2
17
0
Order By: Relevance
“…In a recent meta-analysis on stent-retriever thrombectomy of BAO, pooled mortality was 29.4% 9. Successful recanalization is fundamental for reducing mortality as well as for a good clinical outcome 11 25 26…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis on stent-retriever thrombectomy of BAO, pooled mortality was 29.4% 9. Successful recanalization is fundamental for reducing mortality as well as for a good clinical outcome 11 25 26…”
Section: Discussionmentioning
confidence: 99%
“…81 Successful recanalization has been found not to depend on thrombus length and can be achieved despite a high clot burden. 82 While mechanical thrombectomy in the basilar artery has been associated with more procedural complications than in anterior circulation strokes, 83 failure of successful recanalization was a strong predictor of mortality in a prospective registry of 117 consecutive patients with BAO treated with either stent retrievers or large bore distal aspiration catheters. In the setting of recanalization, a lower pc-ASPECTS (OR 1.71, 95% CI 1.19 to 2.44) and angioplasty/stenting of the basilar artery (OR 4.71, 95% CI 1.34 to 16.54) were independent predictors of mortality after thrombectomy.…”
Section: Emergent Surgical Decompression In Patients With Cerebellar mentioning
confidence: 99%
“…A total of 439 AIS cases that underwent MT were included in the meta-analysis. The measurement of thrombus density was on 5-mm-thickness NECT in most studies, while Shu et al (21) used 2.5-mm NECT and we used 1-mm NECT. Most studies included anterior circulation AIS patients, while Shu et al (21) reported 51 cases of posterior circulation stroke; Jagani et al (22) also included 19 (16%) cases.…”
Section: Resultsmentioning
confidence: 99%